A Simple and Numerically Efficient Valuation Method for American Puts Using a Modified Geske-Johnson Approach. - Bunch, David S; Johnson, Herb (Journal of Finance, 1992)
R. Geske and H. E. Johnson (1984) develop an equation for the American put price and obtain accurate prices using a method requiring quadrivariate normal integrals evaluated over an interval containing four equally spaced exercise points. The authors show that a modification of their method, which uses optimal placement of exercise points, yields, in most cases, accurate values using nothing more than bivariate normals. In the more difficult (deep-in-the-money) cases, trivariate normals suffice.